PERSEPSI GURU TERHADAP PENILAIAN AKREDITASI OLEH BAN-S/M DI MADRASAH IBTIDAIYAH DARUL MUBTADIN: Teachers’ perceptions of accreditation assessment by the National Accreditation Board for Schools/Madrasahs in Madrasah Ibtidaiyah - Kohar, Abdul; Wahyuri, Uyun; Kohar, Dadun Abdul; Maftuh, Dadin Arif (Epistemic: Jurnal Ilmiah Pendidikan, 2025)
Accreditation assessment by the National Accreditation Agency for Schools/Madrasahs (BAN-S/M) is an important instrument in improving the quality of education. However, its implementation often faces challenges, such as complex preparations and limited resources. This study uses a qualitative approach with a case study design to explore teachers' perceptions of the implementation of accreditation at Madrasah Ibtidaiyah Darul Mubtadin Kp. Cipeundeuy. Data were collected through in-depth interviews, direct observation, and document analysis. The results show differences in perceptions among teachers. Some teachers view accreditation as a motivation to improve the quality of learning and professionalism, while others consider the process burdensome due to administrative burdens, lack of incentives, and uneven distribution of resources. The madrasah received a C accreditation, which had an impact on its attractiveness to prospective students, even though student discipline remained high. These findings emphasize the need for more equitable and contextual accreditation policies, accompanied by government support to strengthen teacher welfare and improve the quality of education in madrasahs. Accreditation designed with the actual conditions of schools in mind can be a means of professional development for teachers while also increasing public trust.